(untitled) (TEL Tempo, Espaço e Linguagem, 2025)
Death, as a universal experience, finds new mediations and representations on the internet. This article aims to explore user interactions in posts that disseminate obituaries on the internet through Facebook reaction emojis. To this end, through netnography, it was possible to map news on pages that publicized obituaries from various social strata. The results show that the posts mobilize a wide range of emotions and engagements regarding certain deaths and ways of dying. The conclusion points to cybermutirões (collective online mourning efforts) in funeral announcements, distributed widely but unevenly in the virtual environment.